Characterization of antibiotic resistance genes and virulence factors in organic managed tea plantation soils in southwestern China by metagenomics - Yu, Taobing; Cheng, Lang; Zhang, Qing; Yang, Jida; Zang, Huadong; Zeng, Zhaohai; Yang, Yadong (Frontiers in Microbiology, 2025)
Sustainable organic management practices have gained significant attentions for its potential health and environmental benefits. However, the spread of antibiotic resistance genes (ARGs) and virulence factors (VFs) in soils, plants, and agricultural products has severely limited the development of organic managements on agriculture. At present, the distribution and assembly of ARGs and VFs in organic managed tea plantation systems remains largely unknown. Here, we used metagenomic analysis to explore soil microbial taxa, ARGs and VFs in 20 years of conventional managed (CM) and organic managed (OM) tea plantation soils. Results showed that total abundance of ARGs in OM was 16.9% (p < 0.001) higher than that in CM, and the increased ARGs were rpoB2, evgS, MuxB, TaeA, and efrA. As for VFs, OM significantly increased the abundance of adherence, stress protein and actin-based motility compared to CM. Moreover, OM increased the relative abundance of soil microbial taxa harboring ARGs and VFs, which were Streptomyces, Pseudomonas, and Terrabacter, compared to CM. Network analysis suggested that OM increased the positive interactions of microbial taxa-ARGs, microbial taxa-VFs and ARGs-VFs compared to CM. Impact of stochastic process on the assembly of soil microbial taxa, ARGs and VFs in OM was stronger than that in CM. Overall, these findings provide a basis for integrating ARGs, VFs and pathogen hosts to assess the ecological and health risks in long-term organic managed soils, and increased efforts need to be done in reducing ARGs, VFs and bacterial pathogens in fertilizers for organic managements on agriculture.